A phenomenological study of the meaning and essence of divorce amongst Iranian male drug addicts - Tavallaei, Mehdi (2013)
Divorce and addiction play an important role in individual and family life. Despite their high significance and increasing impact, the society is not taking serious steps for stopping their growth. Their common consequences and unique impacts demand the simultaneous study of these two phenomena. To obtain a deep understanding of Iranian male addicts, whose substance usage makes them face serious family problems and finally divorce, a transcendental phenomenological study was carried out to answer the question, “What is the meaning and essence of divorce amongst Iranian male addict?” This study took place in Yazd province in Iran. Two groups of participants were selected from those with official divorce files in Iranian National Drug Control Headquarter and Social Welfare Organization. Each group consists of five individuals. The first group of men had filed for divorce and in the second group, wives had filed for divorce. In-depth, semi-structured interview and face-to-face communications were the methods used. The Stevick-Colaizzi-Keen method was selected for analyzing data due to its practical approach. Through the individual description and synthesis of textural and structural data, the results were drawn out. Main findings revealed the divorce experience as paradoxical, with a confusing, harsh and complicated structure. These two different groups described the meaning of divorce differently. For the first group, divorce was an important sign of freedom, comfort and peace whereas the second group described it with negative perceptions. Such differences in meaning ascribed to divorce are rooted in various factors such as personal and social characteristics; past experiences; family and societal culture; attitude; problems; level of support; and personal preparedness as evidenced by whether one had filed for divorce himself or had his wife file against him. Practical suggestions for rescuing families from collapse come from understanding the meaning and essence of divorce. Based on the results of this study families can be rescued from collapse if important elements are identified at the appropriate time. Three transition phases include inception, dependency and Family collapse are formed by highlighting the study’s themes factors. Understanding each phase enables family and counselor to help and save addict and preserve the family structure. The Belief- Based Module was formed as a second finding based on integration of participants' ideas about the influence and role of spiritual and religious beliefs on addiction in the present study. The purpose was to provide the possibility of control and to return the addict to normal life- its efficacy was examined in one rehabilitation center in Iran. Based on the first cluster of themes in the data, the New Life Skill Program was designed. This program gives individuals the opportunity to elevate their behavior in coping with life challenges and rescue themselves from drowning. It would be possible in the early stage to stop and prevent the individual from approaching the threats that will ruin his future life. This program, once complete may help facilitate changes to governments and to mass media, related laws, and ads regarding the threats of drug to families respectively.